Case Study of Delay Construction Projects in Bidau Dili Timor-Leste Bridge - Eliseu Soares Parerira Amaral (IJTI International Journal of Transportation and Infrastructure eISSN 2597-4769 pISSN 2597-4734)
The process of implementing development projects has many obstacles that were not predicted beforehand resulting in delays in project completion which have an impact on increasing the cost of project implementation. sometimes the project is not completed in accordance with a predetermined schedule that may be caused by certain factors. Various ways can be done to anticipate and be a solution to the delay. The purpose of the study is to analyze the factors that influence delays in bridge construction projects in Bidau Timor - Leste and how to anticipate delays in project work. The research method used is descriptive method by observation and direct interviews. So that there are several dominant factors that influence the delay of the Bidau Timor-Leste bridge construction project, including the types of weather, material and financial. To anticipate delays in construction projects, it is necessary to do a work contract in accordance with the contract law in which all matters are regulated, so that the anticipation, mitigation and accountability are clear. Identification of the application of overcoming delays in the Bidau Timor-Leste bridge construction project if viewed from the side of the existing contract there are still shortcomings, so it needs to be improved in terms of working contract documents and refer to the contract law.